Traffic Analysis Attacks Over Networks of Anonymous Communication - Parul, Parul; Sharma, Narinder (International Journal of Computer Sciences and Engineering, 2025)
The Infrastructure of Onion routing has major feature which is its flexibility and that is common to all kind of distributed systems. The Onion routing approach offers anonymous data transfer scheme worldwide. The traffic analysis method can be used to break anonymity of the anonymous network, for example TORs (The Onion Routing). Traffic confirmation attacks in low latency networks, mixing networks and in other similar networks are active fields of research. The main idea behind this research is traffic confirmation and analysis of attacks in anonymous communication. Traffic confirmation attacks are used in this research to make successful analysis of traffic of communicating parties over anonymous communication on Internet. It is described in detail that the nature of dropping the packets of Tor Protocol (the onion router) can put anonymity in danger and can harm it. In this paper advantage has been taken of forward compatibility feature by TOR to perform a new drop mark attack and also explained about different traffic confirmation attacks